Dual-energy CT-derived virtual noncalcium imaging to assess bone marrow lesions in patients with knee osteoarthritis - Wei Chen; Limin Liu; Heng Zhao; Hui Li; Jing Luo; Yao-lin Qu; Dan Zhang; Ya-han He; Yi-sha Pan; Fang Gao; Hua-zhi Liao; Xiao-long Chen; et al. (Scientific Reports)
Abstract To determine the diagnostic performance of dual-energy CT (DECT) virtual noncalcium (VNCa) technique in the detection of bone marrow lesions (BMLs) in knee osteoarthritis, and further analyze the correlation between the severity of BMLs on VNCa image and the degree of knee pain. 23 consecutive patients with clinically diagnosed knee osteoarthritis were underwent DECT and 3.0T MRI between August 2017 and November 2018. Evaluation of two pain assessment scales (WOMAC and KOOS) were collected. VNCa images and MRI were independently scored by three readers using a four-level scoring system over 15 anatomical subregions in each knee joint. Spearman correlation coefficient was used for total BML scores on DECT and MRI correlation with WOMAC and KOOS. Specificity, Sensitivity, NPV and PPV of reader 1 and reader 2 were 99.4%/99.2%, 89.4%/87.2%, 98.6%/98.3% and 95.5%/93.2%. A cutoff value of − 41.5 HU/− 46.5 HU provided sensitivities of 93.2%/90.9% and specificities of 100.0%/93.9% for diagnosing BMLs with AUC of 0.970/0.996. A stronger correlation was observed between the WOMAC and total BML score compared to the KOOS. DECT possessed excellent diagnostic performance in the detection of BMLs in knee osteoarthritis. And the pain degree increased with the severity of BMLs on VNCa images.